Vanno: A Visualization‐Aided Variant Annotation Tool. Issue 2 (February 2015) - Huang, Po‐Jung; Lee, Chi‐Ching; Tan, Bertrand Chin‐Ming; Yeh, Yuan‐Ming; Huang, Kuo‐Yang; Gan, Ruei‐Chi; Chen, Ting‐Wen; Lee, Cheng‐Yang; Yang, Sheng‐Ting; Liao, Chung‐Shou; Liu, Hsuan; Tang, Petrus
<x xml:space="preserve">Abstract</x> Vanno supports almost all disease‐associated gene tests and exome sequencing panels designed for NGS, providing a complete solution for targeted and exome sequencing analysis. Vanno also integrates information from biomedical databases, functional predictions from available evaluation models, and mutation landscapes from TCGA cancer types. A highly integrated framework that incorporates filtering, sorting, clustering, and visual analytic modules is provided to facilitate exploration of oncogenomics datasets at different levels, such as gene, variant, protein domain, or three‐dimensional structure. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>